Determinants of Transfer Pricing Risk at the Operating Profit Margin Level: Evidence from Foreign Direct Investment Firms in Indonesia - Yulian Tri Darmawan; Noer Azam Achsani; Bayu Bandono (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
This study investigated the determinants of transfer pricing risk at the operating profit margin level among foreign direct investment companies. The research addresses whether multinational ownership structures and affiliated transaction types contribute differently to profitability deviations relative to comparable independent firms. Using panel data from 131 foreign-owned companies (318 firm-year observations) during 2020–2024, the study applies a random effects model with robust standard errors, complemented by FGLS and System GMM for robustness checks. The findings show that foreign ownership, intangible goods transactions, intercompany loan transactions, and leverage have positive and significant effects on transfer pricing risk, while business turnover has a negative effect. Tangible goods and service transactions, as well as the number of related entities, do not exhibit significant effects. The results indicate that transfer pricing risk is concentrated in transactions characterized by valuation discretion and financial structuring complexity. By employing operating profit margin-based comparability analysis as a measurable risk indicator, this study contributes empirical evidence to support risk-based tax supervision strategies and highlights high-risk transaction categories for more targeted transfer pricing audits.